INCREASING VOCABULARY MASTERY OF VIII GRADE STUDENTS AT MTS. HAJI HAYYUN SALUMPAGA THROUGH VOCABULARY CARD - Marzuki Marzuki; Diyenti Rusdin (Jurnal Madako Education, 2020)
This research is pre experimental research design consist of one group pre-test and post-test. The Population of this research is the Eight grade of MTs. Haji Hayuun Salumpaga in 2016/2017 academic year. The sample of this research is selected by using purposive sampling technique and the selected class is VIII B consisted of 24 students. In collecting the data, the researcher took from pre-test and post-test. The researcher analyzed the data by using SPSS program 16,0 . The result of the test showed that the students’ mean score in posttest 88.58 is higher than pretest 44.42. To know the significant difference between pretest and posttest, the researcher compared the value of t-counted and t-table by applying 0.05 level of significance for two-tailed test with 23 degree of freedom (24-1=23), the researcher found that the tcount (11.956) is higher than ttable (2.069) and the hypothesis of this research is accepted. The researcher concluded that using vocabulary card can increase students’ vocabulary mastery at Eight grade of MTs. Haji Hayyun Salumpaga.Keywords: Vocabulary Mastery, Vocabulary Card.